How Social Media is Shaping Conflicts: Evidence from Contemporary Research - Shams-ur-Rehman; Dr. Saqib Riaz (Journal of Peace, Development and Communication, 2021)
The growing use of social media in contemporaneous conflicts and its penetration into modern warfare is a thing to be pondered. Social media has redefined social movements, collective actions, and empowered marginalized groups to have a say in international affairs. While there has been a large body of literature examining how the traditional media depicts conflicts and violent events, the role of social media in shaping conflicts has been overlooked. Consulting an extensive literature related to social media and contemporary conflicts, this study explored the pivotal role of social media in the escalation of recent civil uprisings and the consequences of digital activism on changing conflict dynamics. This study also analyzed the usage of social media by militant organizations and insurgent groups for their vested interests and validated the insurgent public sphere role of social media in shaping conflicts.